Message - Al-Shamahy, Prof. Dr. Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2022)
Peer review and its importance in evaluation for pharmaceutical and medical journals Peer review, which is the evaluation of work by one or more persons who have similar qualifications to the producers of work on which our beloved journal (UJPR) has relied from the first day of its inception. This method works as a form of self-regulation by members who are qualified for a profession in the relevant field and our journal has selected senior professors and Doctors in the various branches of medical and pharmaceutical sciences. What distinguishes the scientists of our journal is the seriousness and credibility, as well as the quick response in a timely manner. From my experience with many sober medical journals, one of the most disadvantages that these journals suffer is the long response time for review. Undoubtedly, peer review methods are used to maintain quality standards, improve performance and provide credibility, but this does not justify the long delay in reviewing and responding to these journals. A well-known rule of peer review is that in academia, peer review is often used to determine the suitability of an academic paper for publication and our journal adheres to this approach to this day. In addition, it has also been used as an educational tool to help journal publishers and researchers improve their writing assignments for them in the future as corrections in revised articles explaining the reasons for corrections are kept in the journal website and returned to researchers. The professional peer review of our journal has focused on the performance of professionals, with the aim of improving the quality of our journal, and adhering to standards, to obtain evaluation certificates for our journal from specialized bodies and circles such as Scopus. I recommend to my colleagues, students, and researchers from all corners of the globe to publish in the UJPR esteemed journal, which adopts a professional peer review process, which will determine when the article submitted has met the required medical standards and assure them of a professional and scientific response in a timely manner.